Perbedaan Angka Kejadian Nyeri Muskuloskeletal Antara Pria Dan Wanita Pada Kelompok Tani Nira Di Dusun Ngudi Mulyo Pajangan Bantul - ARDYATMA, Cristyan (2015)
Background : Pain disorders resulted by any damage such as muscle spasm, inflammation, degenaration, and bone fractures acommpanied by pain sensation so that reduces the ability of motion. The prevalence of musculoskeletal pain in workers ranged between 6-76% for a year. The prevalence of musculoskeletal pain is higher in female than in male. Objective : The objective of this research is to determine whether there is a difference in the incidence of Musculoskeletal Pain between male and female in Nira's Farmer Group at Ngudi Mulyo, Pajangan, Bantul. Methods : This research has been used an analytic observational study by cross sectional approach. The sampling method was purposive sampling found 84 people. The data analysis was Mann-Whitney test. Result : Male Nira's farmer mostly had a mild pain 64,3%, while female Nira's farmer was 66,7 %. The results of this research showed a statistically significant difference in the incidence of musculoskeletal pain between male and female value p of < 0,0001. Conclusion : This research shows there is a difference in the incidence of musculoskeletal pain between male and female.